Resilience to depression: the role of benevolent childhood experiences in a South African sample - Somefun, Oluwaseyi Dolapo; Theron, Linda; Höltge, Jan; Ungar, Michael (Frontiers in Psychology, 2023)
Background: Studies elsewhere show that benevolent childhood experiences (BCEs) have protective mental health value. However, this protective value has never been investigated in an African context. Given the need to better understand what might support mental health resilience among African young people, this study explores the relationship between BCEs and depressive symptoms among a South African sample of young adults living in a community dependent on the economically volatile oil and gas industry.Methods: A sample of young adults in an oil and gas community in South Africa (N=313, mean age 20.3 years, SD = 1.83, range from 18 to 26; majority Black African) completed selfreport questionnaires to assess BCEs and depressive symptoms (Beck Depression Inventory-II; Beck et al., 1996). The analysis controlled for socio-demographics and experience of family adversity. Multinomial logistic regressions were used to examine the association of BCEs with depressive symptoms using STATA 17.The majority (86.4% of the sample) reported all ten BCEs. Of the ten BCEs, having at least one good friend was the most reported (94%) compared to 75% of the sample reporting having a predictable home routine, such as regular meals and a regular bedtime. The unadjusted multinomial logistic regression analysis indicated that having at least one good friend, comforting beliefs, and being comfortable with self were associated with lower odds of moderate depression. The adjusted results showed no association between BCEs and the depression of young adults in this sample.In this South African sample, our results do not show protective associations between BCEs and depression. This could be because of the homogeneity in our sample. It is also possible that the BCEs explored could not counteract the effect of chronic risk factors in the lives of young people in this study context. Further research is needed to understand this complexity.